Effects of Charismatic Leadership and Professional Leadership on Employee’s Performance in the Public Traditional Chinese Medicine Hospital: A Path Analysis - Zhang, Na; Yang, WenJu; Ali, Anees Janee; Gao, Peiyang; An, XueMei (Journal of Posthumanism, 2025)
Objective: Hospital quality service requirements and outcomes are influenced by the performance of healthcare personnel. Through their leadership skills and work ethic, doctors and nurses are vital to the development and monitoring of healthcare services. This study used work motivation as an intermediary variable to examine how professional and charismatic leadership affected workers’ performance. Methods: Examine how professional and charismatic leadership affects the output of healthcare workers. 1392 employees are included in this quantitative analysis. Path analysis is used to analyze data. The results of the study demonstrated that charismatic and competent leadership improved employee enthusiasm and job performance. One important mediating element was work motivation, which supported the idea that professional leadership produced better performance results than charismatic leadership. Conclusion: Based on managers’ leadership, this study shows that work incentive is essential for improving employees’ performance. In summary, professional leadership may have a greater impact on the quality of healthcare by enhancing employee performance.